A 1‐bit reconfigurable metasurface antenna for ground penetrating radar application. Issue 7 (18th April 2022) - Wang, Ziye; Zeng, Weihua; Zhao, Xiao; Guo, Linyan; Liu, Yan
Abstract: A 1‐bit reconfigurable metasurface antenna for Ground penetrating radar (GPR) application is proposed. The element is loaded with one PIN diode, which can be electronically controlled to generate two states with 200° reflection phase difference at 2.0 GHz. The two states are regarded as "1" and "0." Based on the proposed element, a 10 × 10 reconfigurable metasurface is designed. Besides, a digital control board is used to control the state of element. A reconfigurable metasurface antenna is simulated and fabricated. The simulated and experimented results indicate that the proposed antenna can achieve ±40° beam scanning with a gain tolerance of 3 dB and the maximum gain of 16.7 dBi. In addition, the beam‐forming performance can be achieved, such as multibeam. These properties ensure the proposed antenna has great potential in GPR and microwave imaging systems.